Embedding lightweight proxy re-encryption for efficient attribute revocation in cloud computing. (2016) - Fugkeaw, Somchart; Sato, Hiroyuki
Cloud computing has emerged as a successful paradigm to deliver flexible and convenient data processing and sharing. Security and privacy management of outsourced data is among the top concerns for cloud adoption. To this end, attribute-based encryption primitive has been recognised to achieve secure data access control with privacy preserving of data. However, dealing with the evolution of user attribute and policy update limits the efficiency of attribute-based access control. In this paper, we propose a lightweight proxy re-encryption (L-PRE) technique to enable efficient attribute revocation in collaborative, multi-owner, and multi-authority cloud systems. Our novel L-PRE optimises attribute revocation cost by outsourcing re-encryption key generation to a delegated proxy server in a dynamic and secure manner. In addition, we also introduce key update algorithm to optimise cost for the update of non-revoked users' keys. We also provide the proof to show that our proposed L-PRE scheme is secure under general security model. Finally, a performance evaluation is performed to demonstrate the practicality and efficiency of our proposed scheme.